Between war and peace: The Ottoman economy and foreign exchange trading at the Istanbul bourse - Avni Önder Hanedar; Hatice Gaye Gencer; Sercan Demiralay; Ismail Altay (European Historical Economics Society (EHES), 2017)
Between 1914 and 1918, the Ottoman Empire was involved in the First World War, which caused economic disruptions, huge budget deficits, surmounted inflation rates and excessive devaluation of Lira, the Ottoman currency. Based on the value of Lira against the currencies of three selected countries that were not in the war, we focus on the effects of news about the war on the foreign exchange rates at the Istanbul bourse from 1918 to 1919. Our results signify some dates, which match the official announcements of the war events and/or the official treaties.
Keywords: G1; N25; N45; 330; The Istanbul bourse; foreign exchange trading; the First World War; the armistices; economic recovery